Legal Framework on Protection of Children Against Cyberbully in Malaysia: A Cause of Great Concern - Ayub, Zainal Amin; Mohamed Yusoff, Zuryati; Haq, Md Zahurul (Science and Engineering Research Support Society, 2020)
While modern information technology has brought revolutionary changes in the way people communicate and socialise in one hand, it has become a sophisticated tool for severe violation of privacy and harassment in the other hand. Cyberbullying has become a great concern over the last few decades with rapid development and availability of modern information technology in many parts of the world including Malaysia. Several incidents of online harassments of young children resulting in tragic consequences raised the question as to how to control this menacing phenomenon in online world. As the development of technology is always faster than the governing laws, researchers and legislators finding it difficult to define and answer the legal issues raised by cyberbullying. Specially, in a country like Malaysia where there is no specific legislation to handle perpetration of cyberbullying, authorities must try to find solution in the existing framework of criminal proceeding and social dialogue to protect the children online